Structural Evaluation of Mechanically Alloyed (67-x)Ti-xZr-22Si-11B Powders - Ramos, Alfeu Saraiva [UNESP] (2012)
The present work reports on the structural evaluation of mechanically alloyed Ti-xZr-22Si-11B (x = 5, 7, 10, 15 and 20 at-%) powders. Milled powders and hot-pressed alloys were characterized by X-ray diffraction, electron scanning microscopy, and electron dispersive spectrometry. The Si and B atoms were preferentially dissolved into the Ti and Zr lattices during ball milling of Ti-xZr-22Si-11B (x = 7, 10, 15 and 20 at-%) powders, and extended solid solutions were achieved. The displacement of Ti peaks was more pronounced to the direction of lower diffraction angles with increasing Zr amounts in mechanically alloyed Ti-Zr-Si-B powders, indicating that the Zr atoms were also dissolved into the Ti lattice.